RESPONSIBLE BUSINESS AND SUSTAINABLE DEVELOPMENT the use of data and metrics in the Global South - Mhlanga, David; Dzingirai, Mufaro ([S.l.] : ROUTLEDGE, 2024)
Responsible and sustainable business practices are becoming increasingly important in the information age, as companies are realizing the need to address ethical and social issues associated with their operations. In today's interconnected world, businesses have access to vast amounts of data that can be used to improve their bottom line but can also pose significant risks to individuals and society. At the same time, responsible business practices have the capacity to positively impact international development goals such as poverty alleviation, economic growth, responsible consumption, and health and social welfare. This book presents a transdisciplinary framework for addressing the 2030 Sustainable Development Agenda, offering fresh perspectives from the Global South. It provides an overview of the key challenges and opportunities associated with responsible business practices in the information age, including the need to balance privacy and security concerns with data analytics and innovation. It also highlights some of the best practices and initiatives, such as stakeholder engagement, transparency, and accountability. The book establishes the role of green leadership in promoting responsible production, discusses the importance of measuring and reporting on sustainable innovation, including the use of sustainability metrics and reporting frameworks. Further, it debates the importance of incorporating ethics and sustainability in strategic management practices. It provides a comprehensive understanding of the integration of these values in organizational decisionmaking. By delving into the pressing matters that impact our world today, the book generates a sense of urgency and awareness among its audience. Its inclusive approach to exploring various perspectives and opinions invites readers to participate in a constructive dialogue, broadening their understanding and deepening their empathy for different viewpoints.
Keywords: BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Green Business; Social responsibility of business -- Developing countries; Sustainable development -- Developing countries